A comparative study on the role of microcredit on agricultural production improvement among resource-poor rural women - Namayengo, Faith Muyonga Mayanja; van Ophem, Johan A. C.; Antonides, Gerrit (Frontiers in Sustainable Food Systems, 2023)
The objective of the study was to compare agricultural investment and agricultural production of rural agrarian women in Uganda that had received microcredit to those that had not. A quasi-experimental was used to assess differences between performance indicators of agricultural enterprises for existing and incoming borrowers of Bangladesh Rural and Advancement Committee (BRAC) microfinance. Propensity score matching was used to ensure the comparability of the groups and to assess differences between existing borrowers and in-coming borrowers, before they received their first loan. Results indicated that the major reason for borrowing was education of children. There was no difference in investment in agricultural production between the study groups. The existing borrowers had lower monetary value of all harvested crops and for maize and beans than the in-coming borrowers. Total number of animals owned, types of animals kept and reported monetary value for goats and local cattle were also less for existing borrowers than for in-coming borrowers. It was observed that the loan repayment protocols did not match income from agriculture. The results reveal a need to modify loan repayment protocols to address the latent period between agricultural investment and output.